Abnormal cervical cytology: a risk factor for endometrial cancer recurrence. Issue 3 (1st April 2005) - Brown, A. K.; Gillis, S.; Deuel, C.; Angel, C.; Glantz, C.; Dubeshter, B.
Abstract : The objective of this study was to evaluate the relationship between cervical cytology, histologic type, and risk of endometrial cancer recurrence. We performed a retrospective study of patients undergoing surgery for endometrial carcinoma. Risk factors for recurrence including histology, tumor grade, nodal status, myometrial invasion, peritoneal washings, stage, and cervical cytology were assessed. Abnormal cervical cytology was defined as the presence of any endometrial cells on Pap smear. Papillary serous and clear cell carcinomas were considered high-risk histologies. Univariate and multivariate analyses of risk factors for recurrence were performed. Thirty-nine (9%) patients developed recurrent endometrial cancer. More patients with abnormal Pap smears recurred (12% versus 4%, P < 0.05). For endometrioid adenocarcinoma, abnormal cervical cytology occurred in 61% and 7% recurred, while with high-risk histologies, 84% had abnormal cervical cytology and 19% recurred ( P < 0.05). Other significant predictors of recurrence on univariate analysis were myometrial invasion, nodal status, washings, stage, and histology. On multivariate analysis, only nodal status remained a significant predictor of recurrence. Abnormal cervical cytology is associated with increased risk of endometrial cancer recurrence. Abnormal cervical cytology occurs more frequently in high-risk histologies, which are known to have a higher risk of recurrence. On multivariate analysis, only nodal spread remains a significant predictor of recurrence.